TEACHING THE VOCABULARY OF EMOTION: FOSTERING STUDENTS' EMOTIONAL LITERACY - Yuslimah, Anisa Isti (2016)
Most research under the topic of teaching young learners has been focused on how to promote and master vocabulary in various ways. One thing that seems to have been missed is an exploration of teaching vocabulary in relation to students' emotional literacy which has important position on developing their characters. Thus, the research is aimed at investigating the way(s) in which students foster their emotional literacy through learning vocabulary of emotion and teacher's instructional factors related to the students' vocabulary outcomes. This research used theoretical framework of Social and Emotional Learning from Zins (2004 in Brackett & Rivers, 2016). The qualitative descriptive case study was used focusing on the process of teaching and learning emotional vocabulary through children literature and several activities. Data were collected from several classroom observations in young learner classroom, as well as semi-structured interview with the students. The data show that the teaching of emotional literacy through children literature and several techniques can foster students' emotional literacy. From several techniques that were used in the class, Feeling Face Charades and Watching Movie are the appropriate and interesting techniques for students to get more pictures about feeling and emotion. Students are able to recognize, understand, label, express, and regulate emotion where those are very close to the emotional literacy achievement on children. Thus, it is recommended that teachers should more creative and active to apply various techniques and select the stories to teach the vocabulary of emotion to young learners. ; Sebagian besar penelitian yang berkaitan dengan pengajaran terhadap anak fokus pada bagaimana cara menumbuhkan dan meningkatkan kosa kata dengan berbagai cara. Satu hal yang hampir terlupakan yakni eksplorasi pengajaran kosa kata yang berkaitan langsung dengan pendidikan emosi pada anak dimana hal tersebut memiliki peran penting bagi pengembangan karakter anak. Oleh karena itu, penelitian ini bertujuan untuk menelaah upaya-upaya yang dapat dilakukan untuk menumbuhkan pendidikan emosi pada siswa serta faktor peran guru berkaitan dengan hasil yang didapatkan. Penelitian ini menggunakan pisau analisis dari Zins (2004 in Brackett & Rivers, 2016) tentang framework of Social and Emotional Learning. Deskriptif Kualitatif menjadi fokus dalam proses pengolahan data pengajaran dan pembelajaran pendidikan emosi melalui teks sastra anak dan beberapa strategi yang digunakan. Data-data diperoleh dari observasi di kelas, seperti wawancara bebas dengan beberapa siswa. Data menunjukan bahwa pengajaran pendidikan emosi pada siswa melalui teks sastra serta beberapa strategi yang digunakan dapat menumbuhkan pendidikan emosi pada siswa. Dari beberapa strategi tersebut, Feeling Face Charades dan Watching Movie menjadi strategi yang cocok dan menarik bagi siswa untuk memperoleh gambaran tentang feeling dan emotion. Siswa mampu mengenal, memahami, menamai, mengekspresikan, dan mencocokkan emosi yang telah diketahui sebelumnya dengan yang telah diajarkan. Maka dari itu, peneliti menyarankan agar guru lebih aktif dan kreatif dalam mengaplikasikan strategi serta memilih cerita yang akan dijadikan materi dalam pengajaran pendidikan emosi pada anak.